Essays on religion and human rights: ground to stand on - Little, David (Cambridge University Press, 2015)
Klappentext: "This collection of essays by David Little addresses human rights in relation to the historical settings in which its language was drafted and adopted. Featuring five original essays, Little articulates his view that fascist practices before and during World War II vivified the wrongfulness of deliberately inflicting severe pain, injury, and destruction for self-serving purposes and that the human rights corpus, developed in response, was designed to outlaw all practices of arbitrary force. He contends that while there must be an accountable human rights standard, it should guarantee latitude for the expression and practice of beliefs, consistent with outlawing arbitrary force. Little details the theoretical grounds of the relationship between religion and human rights, and concludes with essays on US policy and the restraint of force in regard to terrorism. With a foreword by John Kelsey, this book is a capstone of the work of this influential writer on religion, philosophy, and law"--